ANALISIS BIMBINGAN BELAJAR SISWA BERKESULITAN MEMBACA SDN 12 PATTE’NE - Hanana Muliana; Hamriani (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
Analysis of Learning Guidance for Students with Reading Difficulties. This study employed a qualitative research design using a descriptive case study approach. The purpose of the study was to describe the forms of reading difficulties experienced by students, identify the factors contributing to these difficulties, and examine the learning guidance provided to students with reading difficulties. The research subjects consisted of three students from Grades II and III at SD Negeri 12 Pattene. The study was conducted during the second semester of the 2025–2026 academic year. Data were collected through observation, interviews, and documentation. To ensure the trustworthiness of the data, the researcher applied credibility, transferability, dependability, and confirmability criteria.The findings revealed that the students experienced various forms of reading difficulties, including an inability to distinguish between letters with similar shapes, difficulty recognizing diphthongs and digraphs, hesitancy when reading syllables, inability to read words, difficulty pronouncing letters within complete sentences, and reliance on spelling words letter by letter. The factors contributing to these reading difficulties included students' low interest in reading, limited parental attention to children's learning activities at home, lack of learning motivation, inadequate and less varied teaching methods and instructional media used by teachers during the learning process, and health-related problems.The study also found that the learning guidance provided for students with reading difficulties at SD Negeri 12 Pattene had not yet been optimal. The school's role in providing guidance services for these students was still limited, and the students' ability to overcome their reading difficulties remained relatively low.